Factors Associated with Clinical Meaningful Recovery after Upper Limb Task-Oriented Training in People with Stroke: A Cohort Study. - Romano, Alberto; Di Meo, Anna; Ferrarin, Maurizio; Thorsen, Rune; Cattaneo, Davide; Bertoni, Rita; Jonsdottir, Johanna (NeuroRehabilitation, 2025)
Background: Task-oriented training (TOT) is a commonly used intervention to improve upper extremity function after stroke. However, predictors of response to rehabilitation for performance and participation remain poorly understood. Aim: To identify baseline predictors of clinically significant upper extremity (UE) recovery across impairment, performance, and participation in individuals post-stroke following TOT. Methods: This is a retrospective study. Sixty-four individuals with stroke were enrolled and received five weeks of inpatient TOT for UE. Baseline characteristics and outcome measures were assessed using the Fugl-Meyer Assessment-Upper Extremity (FMA-UE) for impairment, the Action Research Arm Test (ARAT-15) for performance, and the QuickDASH-9 for participation. Participants were classified as responders and non-responders to the intervention, and binary logistic regression models were developed to predict responsiveness to impairment, performance, and participation measures. Results: All outcome measures showed significant improvement post-intervention. The baseline FMA-UE score, chronicity, and dominance of the involved UE predicted responsiveness for impairment. The FMA-UE score was the main predictor of responsiveness in performance, while no predictors were identified for participation. Conclusions: TOT improved UE impairment and performance in stroke patients, particularly those with moderate baseline impairment. Baseline UE function, chronicity, and dominance were key predictors of responsiveness in impairment and performance. This study highlights the importance of personalized TOT after a stroke. It demonstrates that baseline function, chronicity, and affected limb dominance predict impairment and performance responsiveness to TOT while emphasizing the need to incorporate strategies that facilitate real-world skill transfer and address personal and environmental factors to maximize participation.